O tecnoestresse e o docente durante o ensino remoto emergêncial implantado na pandemia por covid-19 e fatores associados : estudo transversal em escolas médicas da região metropolitana de Belo Horizonte. - Lima, Simone de Paula Pessoa (2022)
Introduction: with social distancing implemented in the first year of the covid-19 pandemic, colleges implemented remote learning (RL) to maintain classes during the suspension of inperson activities. ER uses Information and Communication Technologies (ICTs) as the only instrument of contact with the student, requiring the teacher to adapt to a new social situation, which in itself triggers stress. Objectives: the study sought to identify whether there was stress caused by the use of digital technologies (technostress) among teachers of medical courses, and the associated factors, during remote teaching installed on an emergency basis. Methodology: this is a cross-sectional observational study that was conducted through the application of a self-answered questionnaire by professors of medical courses in the metropolitan region of BH, from November 2020 to July 2021, containing questions that assessed sociodemographic data, technostress (RED/TIC) and technology acceptance (extended TAM). Descriptive analysis and univariate analysis were performed, with differences being verified using Student's t, Pearson's Chi-square and Fisher's exact tests, followed by correlation analysis. Results: the 152 teachers who participated in the study did not present technostress, according to the RED-TIC scale, although some dimensions, when evaluated separately, reached high scores (fatigue). Lower technostress scores were found among those who had previous experience with remote classes, had completed previous training in e-learning, felt prepared and had a positive view of the effectiveness of RL. Higher scores were found among female teachers and among those with worse work contexts, such as: shared space with other family members, overload with domestic work, perceived increase in academic activities and difficulty in organizing the routine. No correlation was observed between acceptance of technology and any of the dimensions of technostress. Conclusion: despite not reaching technostress parameters, the results of the study showed factors that require interventions to reduce teaching stress and, consequently, to favor the continued use of e-learning by institutions.